(untitled) (European Journal of Marketing and Economics, 2021)
Background: A number of reasons are expressed about the importance of foreign direct investment (FDI) in developing countries. FDI increases the investment capital in the host country and transferring of new technologies, conducts the distribution and enlarges the economic productivity, improves the level of competitiveness and exports, develops new markets, etc. Objectives: In this research, the main objective is the economic growth (GDP) analysis in Albania affected by FDI flows and the other fundamental macroeconomic factors of growth/productivity. Methods/Approach: The data in this analysis are time series with quarterly frequencies from 1997 to 2018. The econometric model estimation is multifactor regression of the expanded Solow’s model. Statistical approach base on logarithm and first-order stationarity. Results: Economic growth is a simultaneous phenomenon of FDI, domestic investment, the scale of economic openness (focusing on exports), the aggregate average salary, and the efficient use of public debt, especially external debt. Conclusions: FDI flows are the main factor in total economic productivity, and have a larger contribution to the gross domestic product than domestic investment, per unit invested capital, in Albania.